An Assessment of Deltaplan: The Dutch National Preservation Strategy - de Bruin, Gerrit (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
I am very pleased to be here in this beautiful city, standing before colleagues and friends from the Library sector. In my opinion there are only emotional borders between Libraries, Museums and Archives. In a way we all are facing the same problems, challenges and obligations: ie, how to continue to build and preserve large collections and enhance their accessibility. So I prefer to speak of Institutions, which are helping to preserve the cultural heritage. In my lecture I will tell you about Deltaplan - its successes and its qualified successes. And I also want to tell you about the effects of Deltaplan on the institutions involved. Furthermore, I will tell you something of my own experiences collected during Deltaplan. Owing to the constraints of space, this is, of necessity, a selective appraisal. Libraries where excluded from Deltaplan. They got there own kind of plan in the Metamorfoze project, an initiative of the Netherlands Ministry of Education, Culture and Science and is coordinated by the National Preservation Office of the Netherlands of the Koninklijke Bibliotheek, the National Library of the Netherlands. Documents in archives, objects of art in museums and monuments are threatened by a silent decay. This decay is partly caused by air pollution, light, temperature and relative humidity; fungi, insects and rodents also play their parts; and last but not least by people consulting the original documents or books. Before Deltaplan there were conservation backlogs and no effective management strategies to clear them. Moreover, there were insufficient staff and resources across the sector. Also there were cataloguing backlogs, particularly in the museums. In addition the repositories were inadequate and no proper air conditioning had been installed. Restoration was the common policy in place, to restore materials item by item. As a result there was no overarching conservation plan or policy across the sector, a singular lack of knowledge about the conditions of collections, and consequently no prioritisation.